Agile Processes in Software Engineering and Extreme Programming - Workshops XP 2020 Workshops, Copenhagen, Denmark, June 8-12, 2020, Revised Selected Papers - Paasivaara, Maria; Kruchten, Philippe (Lecture Notes in Business Information Processing,, 2020)
This open access book constitutes the 6 research workshops, the Agile Education and Training Track, the Doctoral Symposium, as well as a panel presented at XP 2020, the 21st International Conference on Agile Software Development, which was held during June 8-12, 2020. The conference was planned to take place at the IT University of Copenhagen, Denmark. Due to the COVID 19 pandemic, the conference was held online. In 2020, the following six workshops took place: Third International Workshop on Software-Intensive Business Eighth International Workshop on Large-Scale Agile Development Second European Symposium on Serverless Computing and Applications Second International Workshop on Agile Transformation First International Workshop on Agility with Microservices Programming Third International Workshop on Autonomous Agile Teams XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends. XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. The 31 papers presented in this volume were carefully reviewed and selected from overall 79 submissions. In addition to the 26 workshop papers, this volume also includes 2 papers from the Agile Education and Training Track and 3 papers from the Doctoral Symposium. Furthermore, the book contains a summary of a panel discussion with the topic "Covid-19's Influence on the Future of Agile".